Development of Smart Packaging Halochromic Film based on Jali Seed Flour (Coix lacryma-jobi) and Kencana Ungu Flower Extract (Ruellia simplex) - Ali Kusrijadi; Zackiyah Zackiyah; Permata Maratussolihah (Jurnal Kartika Kimia, 2026)
The spoilage of marine products such as fresh shrimp is characterized by an increase in pH as a result of protein degradation which produces biogenic amines which are harmful if consumed. Simple early detection of damage can be done using smart packaging halochromic film. The purpose of this research is the synthesis, characterization and ability testing of smart packaging halochromic film is based on jali seed flour (Coix lacryma-jobi) embedded with anthocyanin pigments of Ruellia simplex flower extract (EBRS) as a natural indicator. There are two stages in the research method, the first stage includes the extraction and characterization of anthocyanins from Ruellia simplex flowers. The second stage is the synthesis, characterization and testing of the halochromic film capability of jali seed flour-EBRS film. Measuring Total Anthocyanin Content content in Ruellia simplex flowers extract uses the differential pH methods the anthocyanin is 1.037 mg/L. Sensitivity Test of Ruellia simplex Flower Extract to pH indicate contains pigments and is sensitive to changes in pH from 1-12, and gradual discoloration from magenta to purple, colorless, blue, green, and yellow. Smart packaging halochromic film were made using varying EBRS concentrations of 6%, 8%, and 10% (w/w), The ability of the EBRS halochromic film to change pH from 1 to 12 was obtained by the 8% EBRS halochromic film being the best in inform of discoloration. Characterization of 8% (w/w) EBRS halochromic film compared with standard film showed that the addition of EBRS reduced tensile strength values, increased solubility properties, swelling but did not affect the thickness and water rate transmission properties. The EBRS 8% (w/w) indicator film test showed that the indicator film was able to communicate early detection of shrimp damage.